The relationship between COVID-19 stress and test anxiety in art students: the chain mediating roles of intolerance of uncertainty and sleep quality - Ruiying Liu; Qing Qiu; Baojuan Ye (BMC, 2024)
Abstract Background The global spread of COVID-19 has brought immense physiological and psychological distress to students, such as test anxiety and poor sleep quality. This study aims to explore the relationship between COVID-19 stress and test anxiety and the mediating roles of intolerance of uncertainty and sleep quality between them. Methods A study was conducted in China during the late stage of the pandemic. A total of 936 Chinese art students (age M = 18.51, SD = 2.11, 46.6% female) completed the Coronavirus Stress Measure (CSM), the 12-item Intolerance of Uncertainty (IUS-12), the Brief Version of the Pittsburgh Sleep Quality Index (B-PSQI), and the Test Anxiety Inventory (TAI). A chain mediation model analysis was conducted to examine the mediating effects of intolerance of uncertainty and sleep quality on the association with COVID-19 stress and test anxiety. Results COVID-19 stress was positively associated with test anxiety (β = 0.50, p < 0.001). The intolerance of uncertainty and sleep quality partially and serially mediated the relationship between COVID-19 stress and test anxiety (β = 0.01, 95% CI = 0.01 to 0.02). Conclusion These findings suggest that art students' intolerance of uncertainty and sleep quality partially and serially mediate the relation between COVID-19 stress and test anxiety. The results have significant implications for the intervention and prevention of test anxiety, providing additional evidence for the relationship between COVID-19 stress and test anxiety.